2011
DOI: 10.1111/j.1440-1843.2010.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in idiopathic pulmonary fibrosis: The effect of pulmonary hypertension

Abstract: Background and objective: Increased pulmonary arterial pressure (PAP) usually coexists with impaired lung function in IPF. Data on the effect of pulmonary hypertension (PH) on cardiopulmonary responses during exercise in IPF patients is very limited. We sought to investigate the impact of PH on exercise capacity and the correlation between systolic PAP (sPAP) and pulmonary function testing, as well as cardiopulmonary exercise parameters, in patients with IPF and PH. Methods: Eighty-one consecutive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 31 publications
5
70
0
4
Order By: Relevance
“…GLASER et al [59] reported a significant reduction in exercise capacity in IPF patients with systolic PAP >50 mmHg compared with those with moderate pulmonary hypertension, and a strong inverse correlation between systolic PAP at rest and maximal exercise performance. In the study by BOUTOU et al [60], maximum work rate, peak oxygen uptake, anaerobic threshold, peak oxygen pulse and ventilatory equivalent for carbon dioxide were significantly lower in IPF patients with severe pulmonary hypertension (systolic PAP >50 mmHg) compared with matched patients with mild pulmonary hypertension (systolic PAP 36-50 mmHg) or those without pulmonary hypertension. Also, systolic PAP at rest correlated with indices of gas exchange and circulatory status (peak oxygen uptake, anaerobic threshold, peak oxygen pulse and end-tidal oxygen at anaerobic threshold), but not with defective lung mechanics [60].…”
Section: The Response To Exercisementioning
confidence: 85%
“…GLASER et al [59] reported a significant reduction in exercise capacity in IPF patients with systolic PAP >50 mmHg compared with those with moderate pulmonary hypertension, and a strong inverse correlation between systolic PAP at rest and maximal exercise performance. In the study by BOUTOU et al [60], maximum work rate, peak oxygen uptake, anaerobic threshold, peak oxygen pulse and ventilatory equivalent for carbon dioxide were significantly lower in IPF patients with severe pulmonary hypertension (systolic PAP >50 mmHg) compared with matched patients with mild pulmonary hypertension (systolic PAP 36-50 mmHg) or those without pulmonary hypertension. Also, systolic PAP at rest correlated with indices of gas exchange and circulatory status (peak oxygen uptake, anaerobic threshold, peak oxygen pulse and end-tidal oxygen at anaerobic threshold), but not with defective lung mechanics [60].…”
Section: The Response To Exercisementioning
confidence: 85%
“…When PH is present, it is associated with reduced oxygen pulse at exercise, consistent with haemodynamic limitation [123], with more severe arterial haemoglobin desaturation at exercise [87] and with increased VD/VT, as suggested by an increase in the ratio of minute ventilation (V′E) to carbon dioxide elimination (V′CO 2 ) at the ventilatory threshold [124]. Likewise, correlations exist between the 6-min walk distance and both mPAP and PVR [125].…”
Section: How Do Physiological Alterations Integrate In Ipf? Exercisementioning
confidence: 98%
“…It has previously been demonstrated that PH results in exercise limitation in patients with IPF. 14 Prior work suggests that sildenafi l leads to preferential pulmonary artery vasodilation in well-ventilated lung tissue and may improve ventilation-perfusion matching and gas exchange in IPF. 4 Hence, STEP-IPF hypothesized that sildenafi l treatment would improve exercise capacity in advanced IPF.…”
Section: Discussionmentioning
confidence: 99%